PEMANFAATAN AMPAS TEBU SEBAGAI ARANG AKTIF DENGAN AKTIVATOR LARUTAN BELIMBING WULUH (Averrhoa bilimbi L.) - Kurniasih, Anisa; Pratiwi, Dina Audia; Amin, Muhammad (Ruwa Jurai: Jurnal Kesehatan Lingkungan, 2020)
One of the efforts to utilize bagasse is activated carbon which can be used as an adsorbent for the pharmaceutical industry, foodstuffs, and water purification to remove odors, tastes and colors. So far, the raw materials for making activated carbon use coal and coconut shells, while the activator uses chemicals such as KOH, NaOH, H2SO4, HCl, and others. The manufacture of activated carbon is carried out in three stages, namely the process of dehydration, carbonization, and activation. Bagasse that has been dehydrated for 2 days using sunlight, is carbonized for 1 hour at a temperature of 4500C. Carbon is activated using starfruit extract with a ratio of extract: distilled water, 100%: 0%, 75%: 0%, 50%: 505, 25%: 75%, and the time is varied, namely for 4 hours, 8 hours, 16 hours, and 24 hours.From the research results as much as 4.000 grams of bagasse carbonized to produce 170 grams of carbon. The results of the analysis of the proximate content in bagasse activated carbon have met the Indonesian National Standard (SNI 06–3730–1995), namely the best Total Moisture Content of 2.88%, the best Volatile Matter of 6.88%. The best ash was 3.11%. The best-fixed carbon was 86.30%. The iodine number produced from the bagasse activated carbon is 937.9686 mg / g.The Iodine number has met the requirements of the Indonesian Industry Standard (SII 0258-88), which is more than 750 mg / g, indicating that the activation of activated carbon using starfruit is very reactive. Starfruit can be used as an environmentally friendly activator in making activated carbon.